2014
DOI: 10.1155/2014/240749
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Encryption Frame for Medical Image with Watermark Based on Hyperchaotic System

Abstract: An encryption frame of medical image with watermark based on hyperchaotic system is proposed in this paper. Medical information, such as the patients’ private information, data needed for diagnosis, and information for authentication or protection of medical files, is embedded into the regions of interest (ROI) in medical images with a high capacity difference-histogram-based reversible data-hiding scheme. After that, the watermarked medical images are encrypted with hyperchaotic systems. In the receiving end,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…This section covers the performance comparison of the proposed algorithm on the presented results (under section 3) with the available methods [19,21,47,48,49,50,8,23]. Table 6 provides the comparison analysis in terms of correlation coefficients, NPCR, UACI and entropy.…”
Section: Performance Comparison With the Existing Workmentioning
confidence: 99%
See 2 more Smart Citations
“…This section covers the performance comparison of the proposed algorithm on the presented results (under section 3) with the available methods [19,21,47,48,49,50,8,23]. Table 6 provides the comparison analysis in terms of correlation coefficients, NPCR, UACI and entropy.…”
Section: Performance Comparison With the Existing Workmentioning
confidence: 99%
“…From the table 6, it can be concluded that the proposed chaotic based cryptosystem achieves desirable level of security with highly optimal values than the available methods in the literature[19,21,47,48]. Thus, this work owns comparatively elusive capability of defying statistical and differential attacks.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…It could be inferred that the PSNR values of original and encrypted samples are well within the satisfactory limit of 11 dB. [13,15,16,20,21] in the literature and is reported in Table 6. It could be inferred that the security level of the proposed algorithm is on par with the works reported in the literature but with significant reduction in computational requirements.…”
Section: Peak Signal To Noisementioning
confidence: 55%
“…Medical information, is embedded into the regions of interest (ROI) in medical images with a high capacity difference-histogrambased reversible datahiding scheme. After that, the watermarked medical images are encrypted with hyperchaotic systems proposed by Shun Zhange et al [36].V. Amutha et al [37] has proposed a substitutive watermarking algorithm combined with an encryption algorithm, advanced encryption standard (AES) in counter mode.…”
Section: Joint Watermarkingmentioning
confidence: 99%